The Role of the On-Line Multi-Media Library "Eco-School" in Extracurricular Activities of Students - Truneva, Olga Mikhailovna; Munkoeva, Lyudmila Vladimirovna; Rubtsova, Irina Vladimirovna (Razvitie obrazovaniâ (Online), 2020)
The experience of the urban secondary school on the development and implementation of its own model of the on-line multi-media library of environmental orientation as one of the clusters of multifunctional school information and library center is presented in the article. The purpose of the article is to consider the purpose, objectives, principles, expected outcomes of implementing this model, its structure, components, material and technical parameters and conditions of forming of networking cooperation between educational institutions, ready-to-use possibilities of multi-media library «ECO-school». The authors outline that in general, the multi-media library «ECO-school» is defined as a sphere of media education with special means and methods to ensure the educational process aimed at creating conditions for the implementation of students’ individual trajectories and expanding the digital space of extracurricular activities on the basis of networking cooperation. During the study the following methods were applied: analysis, observation, and comparison. The model developed by the MAEI "Secondary school №26" in Ulan-Ude of the Republic of Buryatia is considered in the article. It is based on the principles of introducing electronic resources based on the school library as a factor that directly affects the quality of education. It is concluded that on the one hand, the multi-media library provides remote access to information resources belonging to other subjects of the information space represented on the Internet. On the other hand, the multi-media library «ECO-school» forms information resources created directly at the school or by members of the network community. In addition, the article provides brief guidelines for the application of the on-line multi-media library resources in students’ extracurricular environment-related activity.